Nitrous oxide emission potentials of Burkholderia species isolated from the leaves of a boreal peat moss Sphagnum fuscum. Issue 12 (2nd December 2015) - Nie, Yanxia; Li, Li; Wang, Mengcen; Tahvanainen, Teemu; Hashidoko, Yasuyuki
Abstract: Using a culture-based nitrous oxide (N2 O) emission assay, three active N2 O emitters were isolated from Sphagnum fuscum leaves and all identified as members of Burkholderia . These isolates showed N2 O emission in the medium supplemented with but not with, and Burkholderia sp. SF-E2 showed the most efficient N2 O emission (0.20 μg·vial −1 ·day −1 ) at 1.0 mM KNO3 . In Burkholderia sp. SF-E2, the optimum pH for N2 O production was 5.0, close to that of the phyllosphere of Sphagnum mosses, while the optimum temperature was uniquely over 30 °C. The stimulating effect of additional 1.5 mM sucrose on N2 O emission was ignorable, but Burkholderia sp . SF-E2 upon exposure to 100 mg·L −1   E -caffeic acid showed uniquely 67-fold higher N2 O emission. All of the three N2 O emitters were negative in both acetylene inhibition assay and PCR assay for nosZ -detection, suggesting that N2 O reductase or the gene itself is missing in the N2 O-emitting Burkholderia . Graphical abstract: : Upon exposure to E -caffeic acid often contained in Sphagnum mosses, N2 O emission by Burkholderia sp. SF-E2 that was isolated as an epiphyte of Sphagnum fuscum was highly accelerated.